Traditional Chinese medicine interventions based on meridian theory for pain relief in patients with primary dysmenorrhea: a systematic review and network meta-analysis - Chen, Shu-Cheng; Ruan, Jia-Yin; Zhang, Bohan; Pang, Lok-Yi; Zhong, Linda; Lin, Shuang-Lan; Wong, Ka-Po; Ouyang, Hui-Xi; Yeung, Wing-Fai; Fu, Qin-Wei; Chen, Bo-Qian (Frontiers in Medicine, 2024)
Objective To determine the comparative effects and safety of traditional Chinese medicine (TCM) interventions based on meridian theory for pain relief in patients with primary dysmenorrhea (PD). Methods This is a systematic review with network meta-analysis. Randomized controlled trials (RCTs) comparing meridian-based TCM interventions with waitlist, placebo, western medicine, and conventional therapies for PD pain. A SUCRA was used to estimate the probability ranking for the effects of interventions. Results 57 RCTs involving 3,903 participants and 15interventions were included. Thirty-two RCTs were rated as low risk of bias. A network diagram was drawn with 105 pairs of comparisons. Compared with NSAIDs and waitlist, significantly better effects were found in acupressure [SMD = −1.51, 95%CI (−2.91, −0.12)/SMD = −2.31, 95%CI (−4.61, −0.02)], warm needling [SMD = −1.43, 95%CI (−2.68, −0.18)/SMD = −2.23, 95%CI (−4.43, −0.03)], moxibustion [SMD = −1.21, 95%CI (−1.85, −0.57)/SMD = −2.10, 95%CI (−3.95, −0.07)], and acupuncture [SMD = −1.09, 95%CI (−1.62, −0.55)/SMD = −1.89, 95%CI (−3.67, −0.11)]. No adverse events were detected. Conclusion For PD pain, the effects of acupressure, acupuncture, warm needling, and moxibustion were superior to those of NSAIDs and waitlist. Oral contraceptive pill, electro-acupuncture, acupressure, and warm needling demonstrated higher probabilities of being better interventions. More high-quality clinical trials are needed to provide more robust evidence of this network. Systematic review registration PROSPERO CRD42022373312.